Analysis of students’ lived experiences in music school: where does the meaning of learning hide? - Volbikienė, Asta; Bubnys, Remigijus (Social Welfare: Interdisciplinary Approach, 2020)
This qualitative research discloses students’ subjective lived experiences in Lithuanian music school; thus, creating assumptions for implementing meaningful learning in children’s education. Music schools which dominate other non-formal education are not exempted because students’ lived experiences show that learning is given meaning there even before the commencement of formal learning. When formal learning starts, the perception of meaningfulness of learning begins to change. Results demonstrate that usually opposite experiences of those things which are expected are gained after students start learning, and that continuous communication between students and teachers in music schools is an antidote against meaningless teaching and learning.
Keywords: lived experience; meaning of learning; music education; music school; non-formal education of children; school students